Pengaruh Kualitas Pelayanan Publik Terhadap Kepuasan Pasien di Puskesmas Barukku Kecamatan Pitu Riase Kabupaten Sidenreng Rappang - Anti, Ardi; Sellang, Kamaruddin; Lukman, Lukman; Syarifuddin, Haeruddin (Saraq Opat: Jurnal Administrasi Publik, 2025)
This study aims to determine the influence of public service quality on patient satisfaction at the Barukku Public Health Center, located in Pitu Riase District, Sidenreng Rappang Regency. The population of this study consisted of 42 patients who had received services in the past two months. The research involved two variables: variable X (public service quality) and variable Y (patient satisfaction). A simple random sampling technique was employed, involving 42 respondents. This research utilized a descriptive quantitative approach. Data were collected through observation, questionnaires, and literature review. The data analysis techniques included validity and reliability tests using IBM SPSS Statistics 21.0. The results showed that public service quality has a significant influence on patient satisfaction at Barukku Public Health Center. Based on the recapitulation results, 60% of respondents rated the public service quality as "fairly good," and 55% rated their satisfaction level as "fairly good." Furthermore, the ANOVA test revealed an F-value of 21.974 with a significance level of 0.000, indicating a statistically significant effect, as the probability is far below 0.05. The partial test (t-test) showed a t-value of 5.580, which is greater than the t-table value of 2.021, confirming that public service quality has a significant influence on patient satisfaction. The coefficient of determination (R square) was 62%, which suggests a moderate influence, while the remaining 38% is influenced by other variables not examined in this study.